Graphenoxide Cross-Linker Based Potentiometric Biosensor Design for Sarcosine Determination - Ünlüer, Özlem Biçen; Altunkök, Nazire; Özkütük, Ebru B.; Ersöz, Arzu (Protein and Peptide Letters, 2021)
Background: Sarcosine, also known as N-methyl glycine, is a natural amino acid that is an intermediate and by product in glycine synthesis and degradation. Recently found in many peptides, sarcosine has been researched as a newly accepted prostate cancer marker. The increased concentration of sarcosine in blood serum and the urine showed that malignancy of measured prostate cancer cells is active. Objective: In this article, we aimed to design a potentiometric biosensor for detection of sarcosine with a low detection limit, high selectivity, short response time, wide linear range, and satisfactory long-term stability. Methods: In this article, we developed a new Graphene oxide (GFOX) photosensitive cross-linker based potentiometric biosensor based on the AmiNoAcid (monomer) Decorated and Light Underpinning Conjugation Approach (ANADOLUCA) method. The functional groups determined using Raman, FT-IR, XPS analyzes, and surface characterization, the morphology of synthesized GFOX photosensitive cross-linker were determined by TEM and AFM studies. Then, the performance of the GFOX based potentiometric biosensor has been evaluated. Results: When the usage of the developed GFOX doped potentiometric biosensor against sarcosine determination, it was found that 10-4 mM sarcosine was determined in 60 seconds in the solution. In addition, the detection limit of the GFOX doped potentiometric biosensor was found to be 9.45x10-7 mM, and the linear potentiometric biosensor was found to be in the concentration range of 10-1 to 10-5 mM. The selectivity studies of the developed potentiometric biosensor were investigated using glycine solutions, and it was determined that GFOX doped potentiometric biosensor was more selective against sarcosine. Besides this, a reusability test using 10-3 mM sarcosine solution showed that reproducible studies were performed without the loss of potential of designed potentiometric biosensor and no loss of sensitivity. Conclusion: After applying the framework, we get a new potentiometric biosensor for sarcosine determination. GFOX photosensitive cross-linker was used in designing potentiometric biosensors, and this increased the stability and efficiency of the biosensor. Therefore, the developed potentiometric biosensor for sarcosine determination could be easily used for the early diagnosis of prostate cancer.
Keywords: potentiometric sensor